2019
DOI: 10.1590/fst.39317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cow, goat, and buffalo milk on the characteristics of cream cheese with whey retention

Abstract: Although cow milk is the most widely used dairy product, the milk of other animals presents characteristics relevant to the development of these products. Goat milk has higher digestibility and a lower incidence of allergic reactions than cow milk, while buffalo milk has higher levels of lipids, proteins and lactose. The objective of this work was to elaborate and evaluate the physicochemical, technological, microbiological and sensory characteristics of cream cheese formulations elaborated with different prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In our study, there was no difference between the culture type and microencapsulation method in terms of matrix structure of the cheese produced. Although the observed matrix structure showed slight differences during the storage period depending on the saline ratio, storage temperature and the water ratio in the mass, the mass maintained the matrix structure in which the casein micelles and its other components are being bound (Fangmeier et al, 2019). In cheese samples to which probiotic bacteria have been added in free form, it has been determined that they attach to the outer surfaces of the matrix, and microcapsules containing probiotic bacteria are capsular in the matrix structure (Figure 1).…”
Section: The Appearance Of Probiotic Microcapsules and Symbiotic Microcapsules Obtained By Extrusion Methods In Cheese Massmentioning
confidence: 94%
“…In our study, there was no difference between the culture type and microencapsulation method in terms of matrix structure of the cheese produced. Although the observed matrix structure showed slight differences during the storage period depending on the saline ratio, storage temperature and the water ratio in the mass, the mass maintained the matrix structure in which the casein micelles and its other components are being bound (Fangmeier et al, 2019). In cheese samples to which probiotic bacteria have been added in free form, it has been determined that they attach to the outer surfaces of the matrix, and microcapsules containing probiotic bacteria are capsular in the matrix structure (Figure 1).…”
Section: The Appearance Of Probiotic Microcapsules and Symbiotic Microcapsules Obtained By Extrusion Methods In Cheese Massmentioning
confidence: 94%
“…Considering the nutritional composition and high treatment cost of cheese whey and whey permeate (Mollea et al, 2013), technologies and new applications are sought to use these by-products, e.g. as ingredients for the formulation of different dairy products (Fangmeier et al, 2019;Guimarães et al, 2018Guimarães et al, , 2019Monteiro et al, 2018Monteiro et al, , 2020Trindade et al, 2019).…”
Section: Ricotta Whey Supplemented With Gelatin and Collagen For The mentioning
confidence: 99%
“…Research related to goat milk has also indicated that its proteins as well as the peptides produced from them have important biological activity such as antimicrobial, immunomodulator, antioxidant, hypocholesterolemic and antihypertensive activities (Medeiros et al, 2018;Mal et al, 2018). It has better digestibility, greater bioavailability of iron and magnesium and higher calcium and copper content than bovine milk (Lucatto et al, 2020;Fangmeier et al, 2019). The composition of long-chain fatty acids in its fraction of monounsaturated and polyunsaturated fatty acids (ω-6 and ω-3 fatty acids, eicosapentaenoic acid-EPA and docosahexaenoic acid-DHA, and medium-chain triglycerides) present in goat milk which are considered beneficial to human physiology surpasses bovine milk, (Hodgkinson et al, 2018); and is also rich in niacin, thiamine, riboflavin, and pantothenate (Ranadheera et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Caprine (goat) milk also possesses potential for successful delivery of probiotics, and despite its less appealing flavor in some products, the use of goat milk as a probiotic carrier has rapidly increased over the last decade (Ranadheera et al, 2019). Dairy products with goat milk have been developed, as for instance yogurt (Hadjimbei et al, 2020), 'dulce de leche' (Chaves et al, 2018), cheese (Shabbir et al, 2019;Özturk & Akin, 2018), cream cheese (Fangmeier et al, 2019) and fermented reconstituted whey (Santos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%